다문화가족지원센터 이용자 만족도 척도 개발 - 김경은(Kyoung Eun Kim); 임정하(Jung Ha Lim); 강복정(Bogchong Kang); 조은영(Eun Young Jo) (Korean Journal of child studies, 2016)
Objective: The purpose of this study was to develop and examine the psychometric properties of the Client Satisfaction Questionnaire on multicultural family support services. Methods: The Client Satisfaction Questionnaire was designed to address key elements of the client's satisfaction with the services (i.e., family education, gender equality education, human right education, and social integration education) provided for multicultural families. The nationwide data were collected from 5,335 clients who participated in family education, 4,582 clients who participated in gender equality education, 4,777 clients who participated in human right education, and 5,547 clients who participated in social integration education at the multicultural family support center. Results: In general, the psychometric properties of the Client Satisfaction Questionnaire were satisfactory. Specifically, social validity was supported by 13 professors and local multicultural service center professionals and construct validity was tested and confirmed using a series of exploratory and confirmatory factor analyses. The split-half reliability and internal consistency of the questionnaire were also highly acceptable. Conclusion: The sound psychometric properties of the Client Satisfaction Questionnaire indicates that the it can be a useful tool for evaluating client satisfaction with the services provided by multicultural family support centers.